The reasons for seasons : the great cosmic megagalactic trip without moving from your chair - Allison, Linda (Boston : Little, Brown, 1975)
Stories to read, ideas to think about, and things to make and do--all contributing to an understanding of the seasons and their effect on the earth.
Book Links (A.L.A.).
Booklist.
Library Journal.
7.0
7.0
5-8.
Keywords: Handicraft -- Juvenile literature; Nature study -- Juvenile literature; Seasons -- Juvenile literature; Seasons; Seasons